The 8-week blood sugar diet cookbook - Bailey, Clare; Schenker, Sarah (Atria Paperbacks, 2016)
"Combat diabetes with this essential companion to New York Times bestselling Dr. Michael Mosley's groundbreaking The 8-Week Blood Sugar Diet, featuring over a hundred delicious and healthy recipes. The 8-Week Blood Sugar Diet revealed new, staggering scientific studies on diabetes and demonstrated a revolutionary 8-week plan, including an 800-calorie daily diet, to reverse the disease's effects. Now continue battling diabetes with these simple and delectable recipes that can lower your blood sugar level and help you shed unwanted pounds. Also discover updated nutritional advice, tips for home cooks of every skill level, and detailed menu plans. It's never too late to fight off diabetes, and with the recipes in The 8-Week Blood Sugar Diet Cookbook, it's possible to ensure more long-term health benefits in an easy and effective manner!"--